SEISMIC STRENGTHENING OF EXISTING RC BUILDINGS STRUCTURES USING CONCRETE JACKETING AND FRP MATERIALS (Advances in Civil and Architectural Engineering, 2021)
The need for repairing and strengthening RC buildings and their structural elements occurs when their elements do not possess sufficient strength, stiffness, and/or ductility due to damage mostly caused by earthquakes. Within the scope of this study, special emphasis will be given to RC buildings where the built-in concrete has not achieved the designed concrete class during construction and/or buildings that cannot satisfy the required strength, stiffness, and deformation characteristics particularly in earthquake conditions owing to construction of additional storeys or enlargements. In such cases, it is necessary to repair and strengthen both individual structural elements and whole structures using traditional (concrete jacketing) and innovative (FRP) materials.